CONNECTION OF AMBIVALENCE OF VITAL VALUES WITH SELF-ACTUALIZATION OF THE PERSON - Красильников, Ігор Олександрович (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2016)
In the article results of empirical research on ambivalence connection of vital values with self-actualization of the person are presented. It is underlined, that persons at whom in consciousness the some ambivalent, not realized social values connected with freedom in private life have a low level of such parameters of self-actualization as creation, spontaneity; in dialogue they are more inclined to emotional rigidness, egocentrism, anxiety. As a result of existential frustration values of freedom, the person tries to cope by aspiration to self-knowledge, to understand himself better.